Introduction to the Local Wisdom of the Rokat Tanean Tradition to Improve the Social Emotionality of Early Childhood - Ghausah, Ulfatul; Farida, Siti (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
This research aims to explore and explore the influence of Rokat Tanean local wisdom in improving the social-emotional dimensions of early childhood in RA Nurul Ihsan, East Dempo Village, Pasean Pamekasan. Local wisdom itself is a cultural heritage that has been formed from the experiences and practices of local communities, including in terms of conflict resolution, empathy, and togetherness. This research method uses a qualitative approach with participatory observation techniques and in-depth interviews with educators and parents involved in the implementation of Rokat Tanean in early childhood, The research results show that the consistent and targeted introduction and application of Rokat Tanean local wisdom can have a positive impact on the social-emotional development of early childhood. The implementation of Rokat Tanean in children's daily activities encourages them to interact positively with the surrounding environment, improve communication skills, build empathy, and manage conflict in a constructive way. Keywords: local wisdom, Rokat tanean, social emotionality of early childhood